Thymic crosstalk restrains the pool of cortical thymic epithelial cells with progenitor properties. Issue 6 (13th April 2017) - Meireles, Catarina; Ribeiro, Ana R.; Pinto, Rute D.; Leitão, Catarina; Rodrigues, Pedro M.; Alves, Nuno L.
Abstract : The induction and maintenance of T‐cell tolerance depends on establishment of functionally competent cortical and medullary thymic epithelial cell (TEC) microenvironments. Meireles and colleagues provide evidence that the postnatal cortex harbors cortical and medullary TEC progenitors and their abundance drops with age as result of continual thymic crosstalk. Abstract : Cortical (cTEC) and medullary (mTEC) thymic epithelial cells establish key microenvironments for T‐cell differentiation and arise from thymic epithelial cell progenitors (TEP). However, the nature of TEPs and the mechanism controlling their stemness in the postnatal thymus remain poorly defined. Using TEC clonogenic assays as a surrogate to survey TEP activity, we found that a fraction of cTECs generates specialized clonal‐derived colonies, which contain cells with sustained colony‐forming capacity ( Clono TECs). These Clono TECs are EpCAM+MHCII‐Foxn1lo cells that lack traits of mature cTECs or mTECs but co‐express stem‐cell markers, including CD24 and Sca‐1. Supportive of their progenitor identity, Clono TECs reintegrate within native thymic microenvironments and generate cTECs or mTECs in vivo. Strikingly, the frequency of cTECs with the potential to generate Clono TECs wanes between the postnatal and young adult immunocompetent thymus, but it is sustained in alymphoid Rag2‐/‐Il2rg‐ /‐ counterparts. Conversely, transplantation of wild‐type bone marrow hematopoietic progenitors into Rag2‐/‐Il2rg ‐/‐ mice and consequent restoration of thymocyte‐mediated TEC differentiation diminishes the frequency of colony‐forming units within cTECs. Our findings provide evidence that the cortical epithelium contains a reservoir of epithelial progenitors whose abundance is dynamically controlled by continual interactions with developing thymocytes across lifespan.